Smart Sensorik in der Schwangerschaft: Narratives Review über die Verlagerung der Schwangerschaftsvorsorge in den Smart Home Bereich Smart sensors in pregnancy: Narrative review on the use of smart home technology in routine prenatal care - Bossung, Verena; Kast, Kristina (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2021)
Introduction Today‘s routine prenatal care in Germany includes regular in-person appointments of pregnant women with doctors or midwives. Considering an increasing digitalization of the healthcare sector and in view of the global COVID-19 pandemic, the frequency of in-person visits could be reduced by remote monitoring using smart sensor technology. We aim to give an overview of the current international research on the use of smart sensors in prenatal care and its benefits, costs and resource consumption. Methods For this narrative review, PubMed and Science Direct were searched for clinical trials using smart sensors in prenatal care published in English or German language from 1/2016 to 12/2020. We included studies which addressed the benefits, costs and resource consumption of this innovative technology. Results We identified 13 projects using smart sensors in the fields of basic prenatal care, prenatal care for patients with hypertensive disease in pregnancy and prenatal care for women with gestational diabetes. The projects detected positive effects of smart sensors on health care costs and resource consumption and at least equal benefits for the pregnant women. Discussion and conclusions The current COVID-19 pandemic underlines the need for the introduction of smart sensor technology into German prenatal care routine. Remote monitoring could easily reduce the frequency of in-person visits by half. Smart sensor concepts could be approved as digital health applications in Germany. In order to increase user acceptance, there should not be any additional costs for pregnant women and health care professionals using modern healthcare apps. However, health insurance providers need to invest in smart sensor technology in order to eventually benefit from it.
Keywords: Pregnancy; Prenatal care; Smart sensor; Digitalization; Remote monitoring